2016
DOI: 10.1101/047746
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Transcriptional Lineage of the EarlyC. elegansEmbryo

Abstract: HIGHLIGHTS-RNA-seq on each cell of the early C. elegans embryo complements the known lineage -We measured the zygotic activation specific to each unique cell of the embryo -We identified genes that are functionally redundant and critical for development -We created an interactive online data visualization tool for exploring the data eTOC BLURBC. elegans is a powerful model for development, with an invariant and completely described cell lineage. To enrich this resource, we performed single-cell RNA-seq on each… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 59 publications
2
27
0
Order By: Relevance
“…Between this study, our previous study of the L2 stage (2), and earlier studies of the 1 to 16-cell stage embryos (37,38), a large portion of the early C. elegans life-cycle has now been profiled by single cell transcriptomics. However, more datasets will be needed to complete missing stages, including other larval stages and the adult soma and germline.…”
Section: Discussionmentioning
confidence: 94%
“…Between this study, our previous study of the L2 stage (2), and earlier studies of the 1 to 16-cell stage embryos (37,38), a large portion of the early C. elegans life-cycle has now been profiled by single cell transcriptomics. However, more datasets will be needed to complete missing stages, including other larval stages and the adult soma and germline.…”
Section: Discussionmentioning
confidence: 94%
“…Due to unequal segregation of cell-fate determinant [36] and multiple cell-cell signaling such as Wnt signaling from P2 to EMS [18] and the first Notch signaling from P2 to ABp [38][39] , cells in the early stage usually possess unique identity not only for for their spatial behavior but also for their distinguishable internal transcriptional profiling [40] . Consequently, for "eutely" C.…”
Section: Robust Progression Of Morphogenesis Induced By Division Evenmentioning
confidence: 99%
“…As genome activity changes, so does histone stability; transcriptionally silent regions have more histone stability (Kireeva et al, 2002). In C. elegans embryos, transcription is activated in varying lineages at differing times (Tintori, Osborne Nishimura, Golden, Lieb, & Goldstein, 2016), thus it could be possible to detect these changes by probing histone population dynamics. We have found that gross histone dynamics are canonical (follow that reported in other model systems) in C. elegans with very little variation in differing lineages.…”
Section: Discussionmentioning
confidence: 99%